a Creative Economy: A Culinary Based Environment - Indrayani Indrayani; Wahjoedi Wahjoedi; Djoko Dwi Kusumojanto (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
The ability to manage natural resources and human resources is of particular concern by each government to advance the region. One process to advance this region is to increase the creative economic capacity of its citizens to produce environmental-based culinary products. The purpose of this study was to determine the culinary creative economy with environmental insight in the Mentawir mangrove tourism village community in North Penajam Paser Regency. This study uses a qualitative approach to the type of phenomenology research that is oriented to subjective experiences or experiences that reveal specific phenomena in the Mangrove Tourism Village of Mentawir Village, Sepaku District, Penajam Paser Utara Regency.